CONTENT VALIDATION FOR THE CONSTRUCTION OF A VIRTUAL SITE ON USE OF TOYS IN PEDIATRIC NURSING - Amparito del Rocío Vintimilla Castro; Magda Andrade Rezende (Universidade Federal do Paraná, 2013)
Play makes it possible to care for the hospitalized child in anxiogenic situations. This exploratory, quantitative and qualitative study, undertaken between April 2008 and April 2009, aimed to validate the content on use of the toy in Pediatric Nursing for the construction of a virtual site. The Delphi Technique and the Likert scale were used, the latter with values from 1 to 5 points; the Cronbach alpha co-efficient (α) (≥ 0.7) measured the internal consistency of three dimensions with 24 elements and the percentage compared the agreement among 12 judges. In the first cycle, the judgment of the three domains proposed was surveyed, reaching a Cronbach α of 0.96. The second cycle ascertained a Cronbach α of 0.91 and measured the property and the clarity of 23 elements. The suggestions were grouped and analyzed for them to be accepted or changed. The content proposed was validated, based on meeting the infants' needs.